Improving The Students’ Ability In Writing Narrative Text By Using Fairy Tale Story - Giawa, Igamawati (Pascasarjana Universitas HKBP Nommensen, 2022)
The research question is: “Does the use of fairy tale story improve the students’ achievement inwriting narrative text to the grade X students of SMA N 1 Selesai in 2017-2018 academic year?”.The aims of this research is to find out: “If the use of Fairy tale story improve the students’achievement in writing narrative text to the grade X students of SMA N 1 Selesai in 2017-2018academic year. The subject of this research is the grade X students of SMA N 1 Selesai in 2017-2018 academic year with the total number 32 students. The method used in this research isClassroom Action Research (CAR), which consists of planning, action, observation and reflection.The instruments used to obtained primary data and the secondary data were writing test, the students’observation sheets, and questionnaire of the respondent. To analyze the students scores used theformula of percentage of class (%). The writer and students’ observation sheets were analyzed usingformula of percentage of mean score. The data presented in this study is qualitative data which areobtained from pre-cycle, the implementation, and the reflection of the action. From the result of theresearch, in the first cycle, the amount of the students who passed the test was improve. There were78,12% of students who passed the test. However, it can not indicate the percentage of success. Theweakness of the cycle one was planned to overcome in the second cycle. In the second cycle, it wasfound that the use of Fairy Tale make the students learning effectively through their activeparticipation in learning process, and through Fairy Tale story improved the students’ achievementin writing narrative text. The result of the study in the second cycle, there were 93,75% studentswho passed the test. It was greater the level of criteria of success. It can be concluded that the useof Fairy Tale story improves the students’ achievement in writing narrative text by the grade Xstudents of SMA N 1 Selesai in 2017-2018 academic years.